Strategic talent management in academic libraries: a case study of UiTM Library / Nurul Aida Noor Azizi and Azizi Jantan - Noor Azizi, Nurul Aida; Jantan, Azizi (2024)
This paper examines the innovative talent pool management practices at UiTM Library aimed at enhancing staff skills and competencies. Recognizing the critical value of collective expertise, the library has fostered a culture of continuous learning and information exchange. The Talent Pool program covers ten key subject areas, detailing initial phases, talent selection processes, monitoring mechanisms, and best practices for developing Subject Matter Experts (SMEs). By highlighting these areas, the paper showcases how the UiTM Library effectively develops and nurtures experts who contribute significantly to both the library and the broader academic community. Significant achievements include increasing speed reading instructors from 17 to 52, certifying staff as Microsoft Office Specialists, and promoting active participation in academic writing and conference presentations. Notably, the formation of a 20-member Systematic Literature Review (SLR) team resulted in the development of a microcredential module for the university. These outcomes underscore the importance of strategic talent management in academic libraries, demonstrating the transformation of traditional roles into a dynamic, skilled workforce capable of meeting evolving demands. This paper provides valuable insights for other institutions seeking to implement similar talent management and development strategies.